Sodium alginate hydrogel loaded with cadmium sulfide-iron composite material, preparation method and application thereof
Patent Information
- Application Number
- CN202611086243.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-21
- Publication Date
- 2026-10-23
AI Technical Summary
[0005]为了解决上述技术问题,本发明提出一种海藻酸钠水凝胶负载硫化镉-铁复合材料及其制备方法、应用,旨在解决现有技术中存在的纯CdS材料光生载流子复合速率高、光腐蚀严重的问题
[0016]有益效果,与现有技术相比,本发明采用水热和交联两步操作,无需高温焙烧、无需多步浸渍,条件温和、能耗低、重现性好、适合工业化。利用该制备方法制备得到的产品,能够同时实现能带调控、电荷分离、析氢活性、光腐蚀抑制、交联固定,低成本、高效率。海藻酸钠水凝胶三维网络固定催化剂从根本上抑制了纳米颗粒的团聚,延长了催化剂服役寿命,水凝胶物理屏障有效阻挡了活性氧和腐蚀性离子对CdS的侵蚀。
Smart Images

Figure CN122955522A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of photocatalytic material preparation technology, and in particular to a sodium alginate hydrogel-supported cadmium sulfide-iron composite material, its preparation method, and its application. Background Technology
[0002] Photocatalytic water splitting for hydrogen production utilizes solar energy to directly convert water into hydrogen, making it the most ideal route for green hydrogen production. Cadmium sulfide (CdS) is a typical visible-light-responsive semiconductor photocatalyst with a band gap of approximately 2.4 eV. It can absorb visible light with wavelengths less than 520 nm, and its conduction band potential is negative than the proton reduction potential. It possesses excellent thermodynamic driving force for hydrogen production and is one of the most widely studied materials in the field of photocatalysis.
[0003] However, pure CdS materials have technical limitations that restrict their practical applications: such as extremely high photogenerated carrier recombination rates due to numerous surface defects, electron-hole recombination times on the picosecond scale (far exceeding surface reaction rates), and low quantum efficiency; and severe photocorrosion due to the easy oxidation of S by photogenerated holes in the lattice. 2- This leads to Cd 2+ Dissolution, structural collapse, and rapid decline in activity; powder is prone to agglomeration, difficult to recycle, and has poor stability: nanoparticles have high surface energy, are prone to agglomeration and sedimentation, and are difficult to operate stably in real water bodies (especially seawater) for a long time.
[0004] Therefore, the existing technology still needs further development and improvement. Summary of the Invention
[0005] To address the aforementioned technical problems, this invention proposes a sodium alginate hydrogel-supported cadmium sulfide-iron composite material, its preparation method, and its application, aiming to solve the problems of high photogenerated carrier recombination rate and severe photocorrosion in existing pure CdS materials. Specifically: In a first aspect, a method for preparing a sodium alginate hydrogel-supported cadmium sulfide-iron composite material includes: Provide iron-doped cadmium sulfide composite materials; The iron-doped cadmium sulfide composite material was dispersed in a sodium alginate solution to obtain a mixed solution; The mixed solution was mixed with a ferric ion coagulation bath to obtain the sodium alginate hydrogel-supported cadmium sulfide-iron composite material.
[0006] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. The purpose and beneficial effects of the present invention can be better achieved and realized through the following preferred technical solutions.
[0007] As a preferred technical solution, the method for preparing the sodium alginate hydrogel-supported cadmium sulfide-iron composite material includes the following steps: Cadmium source, iron source and sulfur source are dispersed in solvent to obtain precursor suspension; The precursor suspension was placed in a reaction vessel and subjected to a hydrothermal reaction. After the reaction was completed, the mixture was cooled and separated to obtain the iron-doped cadmium sulfide composite material.
[0008] As a preferred technical solution, the method for preparing sodium alginate hydrogel-supported cadmium sulfide-iron composite material, wherein the cadmium source is selected from at least one of Cd(NO3)2, CdCl2, and CdSO4; the iron source is selected from at least one of Fe(NO3)3 and FeCl3; the sulfur source is selected from at least one of thioacetamide, thiourea, and Na2S; and the solvent is selected from any one of water and alcohol-water mixed solvents.
[0009] As a preferred technical solution, in the preparation method of the sodium alginate hydrogel-supported cadmium sulfide-iron composite material, the molar ratio of the cadmium source, iron source and sulfur source is 1:0.01:1 to 1:0.1:2.
[0010] As a preferred technical solution, in the preparation method of the sodium alginate hydrogel-supported cadmium sulfide-iron composite material, the mass ratio of the iron-doped cadmium sulfide composite material to sodium alginate is 0.005:1~0.2:1.
[0011] As a preferred technical solution, the method for preparing sodium alginate hydrogel-supported cadmium sulfide-iron composite material, wherein the hydrothermal reaction conditions are a constant temperature of 150~170℃ for 10~12h.
[0012] As a preferred technical solution, in the preparation method of the sodium alginate hydrogel-supported cadmium sulfide-iron composite material, the mass-volume ratio of the iron-doped cadmium sulfide composite material to the trivalent iron ion coagulation bath is 1g:5~20mL.
[0013] Secondly, a sodium alginate hydrogel-supported cadmium sulfide-iron composite material is provided, wherein the sodium alginate hydrogel-supported cadmium sulfide-iron composite material is prepared by the preparation method described above.
[0014] As a preferred technical solution, the sodium alginate hydrogel-supported cadmium sulfide-iron composite material is a three-dimensional interconnected porous hydrogel block material with a macroscopic size of millimeters to centimeters and a microscopic microscopic interconnected pore network. Preferably, the sodium alginate hydrogel-supported cadmium sulfide-iron composite material is uniformly loaded with CdS nanoparticles inside, and the CdS nanoparticles have a particle size of 80~150 nm and are in the form of a mixed crystal with cubic and hexagonal phases. Preferably, in the sodium alginate hydrogel-supported cadmium sulfide-iron composite material, the molar ratio of iron to cadmium is 1:1 to 10.
[0015] Thirdly, a sodium alginate hydrogel-supported cadmium sulfide-iron composite material, as described above, is used for photothermal seawater desalination-photocatalytic hydrogen production.
[0016] Beneficial effects: Compared with existing technologies, this invention employs a two-step process of hydrothermal treatment and cross-linking, eliminating the need for high-temperature calcination and multi-step impregnation. The conditions are mild, energy consumption is low, reproducibility is good, and it is suitable for industrialization. The product prepared using this method simultaneously achieves bandgap modulation, charge separation, hydrogen evolution activity, photocorrosion inhibition, and cross-linking fixation, resulting in low cost and high efficiency. The three-dimensional network fixation of the catalyst by sodium alginate hydrogel fundamentally inhibits the aggregation of nanoparticles, extending the catalyst's service life. The hydrogel's physical barrier effectively blocks the erosion of CdS by reactive oxygen species and corrosive ions. Attached Figure Description
[0017] To more clearly illustrate the technical solutions in the embodiments of the present invention or related technologies, the drawings used in the description of the embodiments or related technologies will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0018] Figure 1 shows the XRD patterns of SA, CdS, SA / CdS, and SA / CdS-Fe provided in the embodiments of the present invention; Figure 2 shows the SEM morphology images of pure CdS (A, B) and SA / CdS-Fe (C, D) provided in the embodiments of the present invention; Figure 3 shows the UV-Vis DRS spectra and Tauc band gap diagrams of various samples provided in the embodiments of the present invention; Figure 4 shows a comparison of the photocatalytic hydrogen production (A) and rate (B) of each sample provided in the embodiments of the present invention; Figure 5 shows the photothermal temperature (A), evaporation rate (B), cumulative evaporation (C), and infrared thermal imaging (D) of SA / CdS-Fe with different Fe contents provided in the embodiments of the present invention. Figure 6 is a schematic diagram of the SA / CdS-Fe photocatalytic-photothermal synergistic mechanism provided in the embodiments of the present invention. Detailed Implementation
[0019] The embodiments of the present invention will be described in further detail below with reference to the accompanying drawings and examples. The following examples are for illustrative purposes only and should not be construed as limiting the scope of the invention.
[0020] In the description of this specification, the references to terms such as "one embodiment," "some embodiments," "example," "specific example," or "some examples," etc., refer to specific features, structures, materials, or characteristics described in connection with that embodiment or example, which are included in at least one embodiment or example of the present invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples. Moreover, those skilled in the art can combine and integrate the different embodiments or examples described in this specification and the features of different embodiments or examples without contradiction. All experimental reagents were analytical grade (AR) and were not further purified; the experimental water was laboratory ultrapure water (resistivity ≥ 18.2 MΩ). cm).
[0021] The present invention provides a method for preparing sodium alginate hydrogel-supported cadmium sulfide-iron composite material, comprising: providing an iron-doped cadmium sulfide composite material; dispersing the iron-doped cadmium sulfide composite material in a sodium alginate solution to obtain a mixed solution; and mixing the mixed solution with a ferric ion coagulation bath to obtain the sodium alginate hydrogel-supported cadmium sulfide-iron composite material.
[0022] The process principle of this invention is as follows: First, Fe species are highly dispersed on the CdS surface in the form of 2 to 5 nanometer ultrafine nanoclusters using a hydrothermal method. Fe introduces an intermediate 3d energy level into the CdS band gap. This energy level can act as a trapping center for photogenerated electrons under illumination, extending electron lifetime and effectively suppressing electron-hole recombination. Simultaneously, Fe... 3+ / Fe 2+ The presence of the redox couple provides an additional consumption channel for photogenerated holes, allowing Fe3+ to capture electrons and be reduced to Fe. 2+ Fe 2+ It was subsequently re-oxidized to Fe by the valence band hole. 3+ This reversible cycle effectively consumes a large number of photogenerated holes, significantly suppressing the photocorrosion effect of CdS. Fe modification also constructs an intermediate energy level below the conduction band of CdS, reducing the band gap from 2.3 eV to 2.0 eV and broadening the light absorption edge from 520 nm to the visible-near-infrared region, greatly improving the material's utilization of the solar spectrum. The second step utilizes sodium alginate and Fe... 3+ The coordination crosslinking reaction, the carboxyl groups on the sodium alginate molecular chain blocks and Fe 3+Rapid coordination occurs, forming a classic egg-box model three-dimensional network hydrogel structure, while simultaneously immobilizing CdS-Fe nanoparticles in situ within the network framework. Unlike traditional physical mixing or surface post-loading methods, in-situ coordination cross-linking creates a strong chemical bond between the catalyst particles and the support, with binding forces far exceeding those of physical adsorption, fundamentally solving the problem of catalyst detachment and loss during use. 3+ In this invention, it plays a dual role as both a CdS modifying dopant element and a crosslinking ion of sodium alginate hydrogel. The core concept of this invention is to utilize iron in multiple ways.
[0023] In one embodiment of the present invention, the preparation of the iron-doped cadmium sulfide composite material includes: Step (1) Add Fe(NO3)3·9H2O to Cd(NO3)3·4H3O solution, stir and mix, then add thioacetamide solution dropwise, mix well and form a uniform precursor suspension; Step (2) The precursor suspension is transferred to a reaction vessel for hydrothermal reaction. After the reaction is complete, the mixture is cooled, centrifuged, the precipitate is washed, and then vacuum dried to obtain yellow CdS-Fe (iron-doped cadmium sulfide composite material) powder. It should be noted that, in addition to Cd(NO3)3·4H3O solution, it can also be CdCl2, CdSO4, or a mixture thereof. In addition to Fe(NO3)3·9H2O, it can also be FeCl3; in addition to thioacetamide solution, it can also be thiourea, Na2S, etc.
[0024] In one implementation of the present invention, the hydrothermal reaction conditions in step (2) are: reaction at a constant temperature of 150~170℃ for 12h; the centrifugation, precipitate washing, and vacuum drying conditions are: centrifugation at 8000~10000 rpm for 10min, the precipitate is washed 3 times with deionized water and 2 times with anhydrous ethanol, and the washed product is dried in a vacuum drying oven at 50~70℃ for 12h.
[0025] In one embodiment of the present invention, the molar ratio of Cd(NO3)2·4H2O, Fe(NO3)3·9H2O, and thioacetamide is 1:0.01:1 to 1:0.1:2. Below this range, the reaction cannot proceed effectively, and the iron-doped cadmium sulfide composite material cannot be obtained. Exceeding this range easily leads to raw material waste, and the resulting iron-doped cadmium sulfide composite material will contain other impurities, affecting its performance.
[0026] This invention also provides a sodium alginate hydrogel-supported cadmium sulfide-iron composite material obtained by the above preparation method. This composite material is a three-dimensional, interconnected, porous hydrogel block material with macroscopic dimensions ranging from millimeters to centimeters. It can be directly manipulated with tweezers or a sieve, eliminating the need for complex steps such as centrifugation or filtration. It significantly outperforms traditional nanopowder materials in terms of ease of operation and recovery efficiency. At the microscopic level, it forms a network of interconnected micron-sized pores, ensuring smooth transport of water and reactants and timely extraction of products. The CdS nanoparticles, with a particle size of 80 to 150 nanometers, exhibit a mixed crystalline structure with both cubic and hexagonal phases, uniformly loaded within the hydrogel framework, with each particle encapsulated and protected by a hydrogel film. Iron is highly dispersed on the CdS surface in the form of 2 to 5 nanometer ultrafine nanoclusters. No independent iron crystalline phase peaks are observed in the full X-ray diffraction spectrum, confirming that the iron species exist in a highly dispersed amorphous state. This invention also provides the application of the above-mentioned composite material in photothermal seawater desalination and photocatalytic hydrogen production. It realizes photocatalytic water splitting to produce hydrogen under high-energy photon drive and realizes photothermal interfacial evaporation seawater desalination under low-energy photon drive. The two functions operate synergistically without interference within the same material system.
[0027] The SA / CdS-Fe composite material provided by this invention enables the full-spectrum, graded utilization of solar energy. High-energy photons (UV-Vis, 400~700 nm): absorbed by CdS, exciting photogenerated electrons and holes; electrons are rapidly transferred to active sites via the Fe 3d intermediate energy level, reducing protons to produce hydrogen; holes are consumed by sacrificial agents, inhibiting recombination and photocorrosion; low-energy photons (near-infrared, >700 nm): absorbed by Fe species, converted into local thermal energy through dd transitions and non-radiative recombination, driving rapid evaporation of water at the hydrogel interface, achieving seawater desalination; the three-dimensional porous network fixes particles, inhibits aggregation, accelerates mass transfer, resists photocorrosion, and facilitates recycling; high water retention ensures continuous water supply at the interface, and low thermal conductivity achieves local heat concentration, improving evaporation efficiency; Fe modification enhances charge separation, and the hydrogel strengthens mass transfer and stability, with the synergistic effect of 1+1>2, achieving efficient hydrogen production and stable desalination.
[0028] The above technical solution will be further explained and illustrated below through specific embodiments.
[0029] Example 1: Preparation of SA / CdS-Fe composite material This embodiment fully illustrates the complete preparation process and preliminary sample processing procedure of Fe-modified CdS powder and SA / CdS-Fe composite hydrogel. The raw materials used in the experiment, such as cadmium nitrate tetrahydrate, thioacetamide, ferric nitrate nonahydrate, sodium alginate, sodium sulfide, sodium sulfite, and anhydrous ethanol, are all of analytical grade and can be used directly without additional purification. The experimental process is carried out using conventional laboratory equipment such as electronic balance, magnetic stirrer, hydrothermal reactor, benchtop high-speed centrifuge, vacuum drying oven, and ultrasonic cleaner. The experiment first used a one-step hydrothermal method to prepare a series of CdS-Fe powders. Raw materials were prepared according to different molar ratios of Fe to Cd (1%, 2%, 3%, 10%). Cadmium nitrate tetrahydrate was fully dissolved in deionized water, and the corresponding mass of ferric nitrate nonahydrate was added and stirred until homogeneous. Then, an aqueous solution of thioacetamide was added dropwise and stirred to obtain a precursor suspension. The suspension was placed in a hydrothermal reactor and then placed in an oven. The reaction was carried out at a constant temperature of 160 °C for 12 hours. After the reaction was completed and the mixture was allowed to cool naturally, the solid product was separated using a centrifuge at 9000 rpm. The precipitate was repeatedly washed with deionized water and anhydrous ethanol, and then placed in a 60 mL container. CdS-Fe powders with different iron contents were obtained by drying in a vacuum drying oven at ℃ for 12 hours. Simultaneously, pure CdS powder was prepared as a blank control without adding an iron source. Based on this, the ordered assembly of the composite hydrogel was carried out. Sodium alginate was dissolved in deionized water and stirred to form a viscous solution. The prepared CdS-Fe powder was added and stirred continuously overnight to ensure uniform dispersion of the powder. The mixed solution was then poured into a coagulation bath containing ferric nitrate and allowed to stand for 12 hours, relying on Fe... 3+ A three-dimensional network hydrogel structure is formed through coordination and crosslinking with the carboxyl groups in sodium alginate molecules, allowing CdS-Fe particles to be in situ encapsulated and fixed. After repeated soaking and washing with deionized water, free iron ions and unbound powder particles are removed. The final product, SA / CdS-Fe composite hydrogel, is obtained after vacuum drying for 24 hours. Finally, sample pretreatment is performed before photocatalytic performance testing. 30 mg of powder or block hydrogel sample is dispersed in a mixed sacrificial agent solution prepared from sodium sulfide and sodium sulfite, ultrasonicated for 10 minutes, and then transferred to a sealed photoreactor and evacuated for later use. The entire preparation process is simple and efficient. The one-step hydrothermal method ensures uniform loading and tight interfacial bonding of Fe species on the CdS surface, while utilizing the Fe inherent in the material itself. 3+ It acts as a crosslinking agent, eliminating the need for additional additives, effectively reducing preparation costs, and enabling stable mass production of a series of composite materials with different iron contents.
[0030] Example 2: X-ray diffraction analysis In this embodiment, X-ray diffraction was used to test and analyze the crystal phase structure of pure sodium alginate, pure CdS, SA / CdS composite material, and a preferred ratio SA / CdS-Fe (2.0%) sample. During the testing process, standard diffraction cards for cubic CdS (PDF#10-0454) and hexagonal CdS (PDF#41-1049) were used as references. The changes in crystal phase and the form of elements in the material were comprehensively determined by combining the test patterns and the schematic diagram of the unit cell structure. Figure 1 As shown, the pure CdS sample exhibits characteristic diffraction peaks at multiple locations with 2q values of 23.5°, 31.5°, 38.5°, and 47.5°. These peak positions match those of two standard cards, confirming that the experimentally prepared CdS is not a single crystalline phase, but rather a mixed crystalline structure with both cubic and hexagonal phases. Pure sodium alginate, as a natural polymer, is a typical amorphous substance; its XRD pattern shows only one broad, diffuse peak at 2q ≈ 23.5°, without any sharp characteristic diffraction peaks. When CdS and sodium alginate are combined to form SA / CdS material, the spectrum simultaneously displays the diffuse peaks of sodium alginate and the characteristic diffraction peaks of CdS, proving that CdS is successfully loaded into the hydrogel system. Only one diffraction peak shows a slight shift of approximately 0.5°, a phenomenon caused by a slight lattice strain induced by the interfacial interaction between Cd particles and sodium alginate; the overall crystalline structure remains intact. For the SA / CdS-Fe (2.0%) composite material, only the three main peaks with the highest CdS intensity were retained in the spectrum. The intensity of diffraction peaks at high angles was significantly reduced or even disappeared. This is because the CdS surface is coated with amorphous iron species, which shield and absorb X-rays. Furthermore, no characteristic diffraction peaks of elemental iron or iron oxides appeared in the entire spectrum, indicating that the introduced Fe species did not form an independent crystalline phase, but were highly dispersed on the CdS surface in the form of single atoms or ultrafine nanoclusters. Moreover, the positions of all CdS diffraction peaks did not shift, further proving that the Fe element only modified the material surface and did not enter the CdS lattice. Comprehensive analysis confirms that the iron modification process and hydrogel assembly process used in this invention do not damage the original crystal structure of the CdS matrix, and the material exhibits good crystalline phase stability.
[0031] Example 3: Morphology and Microstructure Analysis This embodiment utilizes ultra-high resolution field emission scanning electron microscopy to observe and analyze the microstructure, particle size, dispersion state, and framework structure of pure CdS powder and SA / CdS-Fe(10%) composite hydrogel samples. Combined with scanning images at different magnifications, the differences in microstructure of the materials before and after modification and assembly are visually compared. Figure 2As shown, unmodified and unassembled pure CdS exhibits an irregular nanoparticle morphology, with particle sizes generally distributed in the range of 80–150 nm. The particle surfaces are relatively smooth, but due to the high surface energy of the nanomaterials, significant agglomeration occurs between the particles. This agglomeration problem greatly reduces catalytic active sites, directly affecting the material's performance. However, after Fe modification and assembly with sodium alginate to form a composite hydrogel, the microstructure of the material changes significantly. Under low magnification, it can be observed that sodium alginate reacts with Fe... 3+ Cross-linking resulted in a complete three-dimensional porous network structure with gel pores reaching the micrometer level. CdS-Fe particles were uniformly encapsulated and anchored within the gel framework, and the gel network isolated the particles from each other, fundamentally suppressing the aggregation of nanoparticles. Under high magnification, the surface of CdS-Fe particles appeared rough, a morphological feature resulting from the deposition of Fe species in the form of tiny nanoclusters on the CdS surface. Simultaneously, each CdS-Fe particle was covered with a thin hydrogel film, which acted as a physical protective barrier, effectively isolating CdS from direct contact with reactive oxygen species in the reaction system and significantly mitigating the photocorrosion defects commonly found in CdS materials. Overall, the modified and assembled composite material exhibited a reasonable microstructure. The porous network structure ensured unobstructed material transport channels while achieving stable fixation of catalyst particles, fully meeting the application requirements of both photocatalytic hydrogen production and photothermal seawater desalination.
[0032] Example 4: Ultraviolet-Visible Diffuse Reflectance Spectroscopy and Optical Bandgap Analysis This embodiment systematically studies the light absorption characteristics of different samples in the 200 nm to 800 nm wavelength range using ultraviolet-visible diffuse reflectance spectroscopy. Simultaneously, the Tauc formula is used to calculate the spectral data, accurately obtaining the optical bandgap values for each sample. The effects of iron modification and hydrogel composite treatment on the material's optical properties, light response range, and band structure are comprehensively analyzed. Figure 3As shown, the light absorption edge of pure CdS is located at 520 nm, and it can only absorb ultraviolet light and short-wavelength visible light, but it cannot respond to long-wavelength visible-near-infrared light. Pure sodium alginate has very weak light absorption throughout the entire test wavelength range, with only a very small amount of absorption in the ultraviolet region, and it is basically transparent in the visible light region. Therefore, using it as a carrier will not interfere with the light absorption process of CdS. The spectral curve of the SA / CdS sample after CdS and sodium alginate composite is basically consistent with that of pure CdS, which also confirms that the sodium alginate carrier has good light transmittance. The optical properties of the SA / CdS-Fe material after Fe modification are significantly optimized. The light absorption intensity in the visible-near-infrared region from 500 nm to 800 nm is greatly improved, and a broad absorption envelope appears in the region from 550 nm to 650 nm. This absorption band originates from Fe. 3+ The dd-electron transitions within the Fe element and the charge transfer effect at the Fe-CdS interface demonstrate a strong electronic interaction between Fe and CdS, successfully extending the material's optical response range into the visible-near-infrared region. Optical bandgap calculations show that the optical bandgap of pure CdS is 2.3 eV, while the bandgap of the Fe-modified SA / CdS-Fe (10%) sample shrinks to 2.0 eV. The core reason for this bandgap narrowing is that Fe modification creates an intermediate energy level composed of Fe 3d orbitals below the CdS conduction band bottom. This energy level effectively traps photogenerated electrons, prolongs carrier lifetime, and suppresses the recombination behavior of photogenerated electrons and holes. In summary, Fe modification effectively optimizes the optical properties of CdS, broadens the material's spectral response range, improves photon utilization, and lays a solid optical foundation for the material to simultaneously achieve photocatalytic and photothermal functions.
[0033] Example 5: Performance Test of Photocatalytic Hydrogen Production Coupled with Photothermal Seawater Desalination This embodiment conducts photocatalytic hydrogen production performance tests and photothermal seawater desalination performance tests to explore the influence of different Fe doping amounts on the two core properties of the composite material. During the photocatalytic hydrogen production tests, a 300 W xenon lamp with a 420 nm filter was used to provide visible light, with a mixed solution of sodium sulfide and sodium sulfite as a sacrificial agent. The reaction was carried out continuously for 5 hours, and the hydrogen production was detected periodically using gas chromatography to calculate the average hydrogen production rate for each sample. The photothermal seawater desalination was conducted under simulated sunlight, with continuous monitoring of sample surface temperature changes for 6 hours, and simultaneous calculation of water evaporation rate and cumulative water loss. Figure 4 As shown, the pure CdS sample exhibits severe photogenerated carrier recombination, exhibits the lowest catalytic activity, and has an average hydrogen production rate of only 0.31 mmol. h -1 g -1After simply combining CdS with sodium alginate to obtain SA / CdS, the hydrogen production rate increased to 0.56 mmol thanks to the improved particle dispersibility of the gel. h -1 g -1 The activity of the material was further enhanced after the introduction of Fe modification; when the Fe / Cd molar ratio was 1.0%, the hydrogen production rate reached 1.01 mmol. h -1 g -1 When the Fe / Cd molar ratio is increased to 2.0%, the material's hydrogen production performance reaches its peak, with an average hydrogen production rate of 1.06 mmol. h -1 g -1 It is 3.5 times that of pure CdS. Further increasing the iron content to 3.0% and 10.0% leads to the formation of new carrier recombination centers within the material due to the excess Fe species, resulting in a gradual decrease in the hydrogen production rate. For example... Figure 5 As shown, the surface heating capacity and moisture evaporation rate of the materials are positively correlated with the Fe doping amount. The higher the Fe content, the stronger the photothermal conversion capacity of the material. After 6 hours of irradiation, the surface temperature of SA / CdS-Fe (1%) was 43.5 ℃, SA / CdS-Fe (2%) was 50.3 ℃, and SA / CdS-Fe (3%) was 55.7 ℃. SA / CdS-Fe (10%) heated up the fastest, reaching a final temperature of 61.8 ℃. The corresponding average moisture evaporation rate also increased with increasing iron content, with the evaporation rate of SA / CdS-Fe (10%) reaching 1.68 kg. m -2 h -1 The photothermal desalination effect is the best. Considering both performance aspects, the high Fe content sample is only suitable for a single seawater desalination scenario, while the sample with an Fe / Cd molar ratio of 2.0% possesses both excellent photocatalytic hydrogen production activity and good photothermal evaporation capacity, thus achieving both functions and representing the optimal ratio for simultaneous solar-powered co-production of green hydrogen and freshwater.
[0034] Example 6: Investigation into the Mechanism of Synergistic Application of Photothermal Evaporation and Photocatalytic Hydrogen Production This embodiment combines the material's microstructure, optical properties, band structure, and various test data to deeply analyze the synergistic mechanism of the SA / CdS-Fe composite material's two major functions: photocatalytic hydrogen production and photothermal seawater desalination, elucidating the inherent logic of the material's ability to achieve full-spectrum, graded utilization of solar energy. For example... Figure 6 As shown, from a structural perspective, relying on Fe 3+The three-dimensional porous hydrogel network of sodium alginate formed by coordination crosslinking can firmly fix CdS-Fe particles, completely avoiding the problems of catalyst particle agglomeration and loss during use. The abundant hydrophilic channels of the gel can accelerate the diffusion rate of seawater to the catalyst surface, while timely exporting the hydrogen and water vapor generated in the reaction, reducing mass transfer resistance. In addition, the gel layer acts as a physical barrier, which can prevent active oxygen species in the system from eroding CdS, effectively inhibiting photocorrosion and improving the cycle life of the material. From the perspective of photoelectrochemical reactions, Fe nanoclusters uniformly dispersed on the CdS surface introduce Fe 3d intermediate energy levels. High-energy visible light photons from sunlight are absorbed by the CdS matrix, exciting photogenerated electron-hole pairs. These photogenerated electrons can rapidly migrate to surface active sites via the Fe-constructed intermediate energy levels, reducing hydrogen ions in water to generate hydrogen gas. Meanwhile, photogenerated holes are promptly consumed by sacrificial agents within the system, further reducing carrier recombination. Low-energy near-infrared photons, which constitute a larger proportion of sunlight, cannot drive photocatalytic reactions but can be absorbed by Fe species. Through dd electron transitions and non-radiative recombination of carriers, light energy is converted into heat energy, increasing the overall surface temperature of the material. This, in turn, drives the rapid evaporation of seawater at the gel interface, completing the seawater desalination process. In this system, the photothermal heating effect can further accelerate the photocatalytic reaction kinetics. These two functions promote each other without interference, ultimately achieving a full-spectrum, graded utilization of solar energy: "high-energy photons for hydrogen production and low-energy photons for thermal desalination." Based on this synergistic mechanism, the material structure can be optimized to prepare a bilayer functional composite material. The upper layer uses a high-Fe content material to enhance the photothermal seawater desalination effect, while the lower layer uses a material with an optimal Fe ratio of 2.0% to ensure the photocatalytic hydrogen production efficiency. This material and its mechanism can be widely applied to integrated equipment for solar hydrogen production and seawater desalination in islands and coastal areas, and has good prospects for practical promotion and industrial application.
[0035] Finally, it should be noted that the above embodiments are only for illustrating the present invention and not for limiting the present invention. Although the present invention has been described in detail with reference to the embodiments, those skilled in the art should understand that various combinations, modifications, or equivalent substitutions of the technical solutions of the present invention do not depart from the spirit and scope of the technical solutions of the present invention and should be covered within the scope of the claims of the present invention.
Claims
1. A method for preparing a sodium alginate hydrogel-supported cadmium sulfide-iron composite material, characterized in that, include: Provide iron-doped cadmium sulfide composite materials; The iron-doped cadmium sulfide composite material was dispersed in a sodium alginate solution to obtain a mixed solution; The mixed solution was mixed with a ferric ion coagulation bath to obtain the sodium alginate hydrogel-supported cadmium sulfide-iron composite material.
2. The method for preparing sodium alginate hydrogel-supported cadmium sulfide-iron composite material according to claim 1, characterized in that, The preparation of the iron-doped cadmium sulfide composite material includes: Cadmium source, iron source and sulfur source are dispersed in solvent to obtain precursor suspension; The precursor suspension was placed in a reaction vessel and subjected to a hydrothermal reaction. After the reaction was completed, the mixture was cooled and separated to obtain the iron-doped cadmium sulfide composite material.
3. The method for preparing sodium alginate hydrogel-supported cadmium sulfide-iron composite material according to claim 2, characterized in that, The cadmium source is selected from at least one of Cd(NO3)2, CdCl2, and CdSO4; the iron source is selected from at least one of Fe(NO3)3 and FeCl3; the sulfur source is selected from at least one of thioacetamide, thiourea, and Na2S; and the solvent is selected from any one of water and alcohol-water mixed solvents.
4. The method for preparing sodium alginate hydrogel-supported cadmium sulfide-iron composite material according to claim 2, characterized in that, The molar ratio of the cadmium source, iron source and sulfur source is 1:0.01:1 to 1:0.1:
2.
5. The method for preparing sodium alginate hydrogel-supported cadmium sulfide-iron composite material according to claim 1, characterized in that, The mass ratio of the iron-doped cadmium sulfide composite material to sodium alginate is 0.005:1 to 0.2:
1.
6. The method for preparing sodium alginate hydrogel-supported cadmium sulfide-iron composite material according to claim 2, characterized in that, The hydrothermal reaction is carried out under constant temperature conditions of 150~170℃ for 10~12h.
7. The method for preparing sodium alginate hydrogel-supported cadmium sulfide-iron composite material according to claim 1, characterized in that, The mass-to-volume ratio of the iron-doped cadmium sulfide composite material to the trivalent iron ion coagulation bath is 1 g: 5~20 mL.
8. A sodium alginate hydrogel-supported cadmium sulfide-iron composite material, characterized in that, The sodium alginate hydrogel-supported cadmium sulfide-iron composite material was prepared using any one of the preparation methods described in claims 1 to 7.
9. The sodium alginate hydrogel-supported cadmium sulfide-iron composite material according to claim 8, characterized in that, The sodium alginate hydrogel-supported cadmium sulfide-iron composite material is a three-dimensional interconnected porous hydrogel block material with macroscopic dimensions ranging from millimeters to centimeters and microscopic dimensions of a micron-scale interconnected pore network. Preferably, the sodium alginate hydrogel-supported cadmium sulfide-iron composite material is uniformly loaded with CdS nanoparticles inside, and the CdS nanoparticles have a particle size of 80~150 nm and are in the form of a mixed crystal with cubic and hexagonal phases. Preferably, in the sodium alginate hydrogel-supported cadmium sulfide-iron composite material, the molar ratio of iron to cadmium is 1:1 to 10.
10. A sodium alginate hydrogel-supported cadmium sulfide-iron composite material as described in any one of claims 8 to 9 for photothermal seawater desalination-photocatalytic hydrogen production.